2017
DOI: 10.1097/mcg.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

Appointment Wait Time, Primary Care Provider Status, and Patient Demographics are Associated With Nonattendance at Outpatient Gastroenterology Clinic

Abstract: Wait time, ethnicity, marital status, and PCP status were associated with missed GI clinic appointments. Further investigations are needed to assess the effects of intervention strategies directed at reducing appointment wait time and increasing PCP-based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
5
19
1
1
Order By: Relevance
“…Furthermore, all categories within marital status had a greater frequency of attenders, which is similar to a study conducted by Shrestha and Hu 22 where the authors found that patients that attended scheduled appointments were mostly married. Alternatively, age was not associated with any particular outcome.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, all categories within marital status had a greater frequency of attenders, which is similar to a study conducted by Shrestha and Hu 22 where the authors found that patients that attended scheduled appointments were mostly married. Alternatively, age was not associated with any particular outcome.…”
Section: Discussionsupporting
confidence: 85%
“…This contrasts with studies in which gender was identified as a factor that influenced non-attendance rates. In two studies, being female was identified as a predictor of non-attendance 21,22 whereas the two studies by Ntamo et al 33 and Langhorne et al 8 found that being male was associated with non-attendance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…21,22 Within gastroenterology, the presence of a PCP at a center has been associated with an increased likelihood of patients attending their outpatient gastroenterology clinic appointments and improved coordination of colorectal cancer screening. 23,24 PCPs also have an expanding role in the management of patients with Hepatitis C and cirrhosis. 2325 However, to our knowledge, the role of PCPs in the management of patients with BE has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…In the outpatient setting, wait time has served as an intuitive focus of study, with longer wait periods thought to correlate negatively with perceived quality of care. 3,4 Still, the patient's perception of unfavorable or unacceptable periods of waiting may be influenced by a myriad of factors unrelated to quality of clinical care. Ordinarily, physicians may not be equipped to balance the individual needs presented by varying patient demographic factors such as race, socioeconomic status, gender, cultural and social norms, or education level.…”
Section: Introductionmentioning
confidence: 99%